Banking in Sub-Saharan Africa: Interim report on digital financial inclusion - Jean-Philippe Stijns; Sofiia Borysko; Barbar Marchitto (European Investment Bank (EIB), 2017)
This report summarizes the discussions held in the context of the Roundtable on Digital Financial Inclusion in Africa during the 2017 EIB Africa Day, which was co-organized in Berlin on July 6th, 2017 by the EIB, Afrika-Verein der Deutschen Wirtschaft and the German Federal Ministry for Economic Cooperation and Development. It aims at providing an interim thematic update in between two editions of the EIB's Study of Banking Sectors in sub-Saharan Africa. – – In dem Bericht werden die Gespräche zusammengefasst, die beim EIB Africa Day 2017 in der Diskussionsrunde über die digitale finanzielle Inklusion in Afrika geführt wurden. Der Africa Day fand am 6. Juli 2017 in Berlin statt. Organisatoren waren die EIB, der Afrika-Verein der Deutschen Wirtschaft und das deutsche Ministerium für wirtschaftliche Zusammenarbeit und Entwicklung. Der Bericht enthält eine thematische Aktualisierung und erscheint zwischen zwei Ausgaben der EIB-Studie über das Bankwesen in Subsahara-Afrika.
Keywords: 330